Adipose-Derived Mesenchymal Stem Cell Facilitate Hematopoietic Stem Cell Proliferation via the Jagged-1/Notch-1/Hes Signaling Pathway - Hongbo Wang; Xiaojuan Bi; Rongyao Zhang; Hailong Yuan; Jianli Xu; Kaile Zhang; Songqing Qi; Xue Zhang; Ming Jiang (Hindawi Limited, 2023)
Background. Poor graft function (PGF) is a life-threatening complication following hematopoietic stem cell transplantation (HSCT). Current therapies, such as CD34+ cell infusion, have shown limited effectiveness. Conversely, mesenchymal stem cells (MSCs) show potential in addressing PGF. Adipose-derived mesenchymal stem cells (ADSCs) effectively support long-term hematopoietic stem cell proliferation. Therefore, this study aimed to investigate the mechanisms underlying the long-term hematopoietic support provided by ADSCs. Methods. ADSCs were isolated from mice and subsequently identified. In vitro experiments involved coculturing ADSCs as feeders with Lin-Sca-1+c-kit+ (LSK) cells from mice for 2 and 5 weeks. The number of LSK cells was quantified after coculture. Scanning electron microscopy was utilized to observe the interaction between ADSCs and LSK cells. Hes-1 expression was assessed using western blot and real-time quantitative PCR. An γ-secretase inhibitor (GSI) was used to confirm the involvement of the Jagged-1/Notch-1/Hes-1 pathway in LSK cell expansion. Additionally, Jagged-1 was knocked down in ADSCs to demonstrate its significance in ADSC-mediated hematopoietic support. In vivo experiments were conducted to study the hematopoietic support provided by ADSCs through the infusion of LSK, LSK + fibroblasts, and LSK + ADSCs, respectively. Mouse survival, platelet count, leukocyte count, and hemoglobin levels were monitored. Results. ADSCs showed high-Jagged-1 expression and promoted LSK cell proliferation. There was a direct interaction between ADSCs and LSK cells. After coculture, Hes-1 expression increased in LSK cells. Moreover, GSI-reduced LSK cell proliferation and Hes-1 expression. Knockdown of Jagged-1 attenuated ADSCs-mediated promotion of LSK cell proliferation. Furthermore, ADSCs facilitated hematopoietic recovery and promoted the survival of NOD/SCID mice. Conclusion. The hematopoietic support provided by ADSCs both in vivo and in vitro may be mediated, at least in part, through the Jagged-1/Notch-1 signaling pathway. These findings provide valuable insights into the mechanisms underlying ADSCs-mediated hematopoietic support and may have implications for improving the treatment of PGF following HSCT.